The Modified Dosages for Acute Malnutrition (MODAM) study: protocol for three integrated randomized controlled trials of novel approaches for the management of childhood wasting in Ethiopia - Indi Trehan; Yosef Beyene; Hiwot Darsene; Bailey S. Adams; Maria Wrabel; Getu Gizaw; Liya A. Legese; Bernardette Cichon; Stanley Chitekwe; Mesfin W. Shellemew; Masresha Tessema; Heather C. Stobaugh (BMC Nutrition)
Abstract Background Only a small percentage of children with severe and moderate acute malnutrition receive treatment due to resource limitations, relatively complex treatment protocols, persistent supply chain challenges, and limited early identification among high-risk populations. Several innovations to the current model of care for uncomplicated acute malnutrition have been proposed, including modified doses of nutritional supplementation and family-led mid-upper-arm circumference (MUAC) and edema screening (“Family MUAC”) for early identification. The evidence base for these innovations remains limited. Methods The Modified Dosages for Acute Malnutrition (MODAM) study includes three integrated individually randomized clinical trials testing innovations in the identification and treatment of acute malnutrition in Ethiopia. One trial will enroll 2400 children aged 6–59 months with severe acute malnutrition, testing standard weight-based dosing of ready-to-use therapeutic food (RUTF) against two experimental RUTF dosing regimens: either two sachets (1000 kcal) daily of RUTF until discharge, or two sachets until achieving anthropometric criteria for moderate acute malnutrition (MAM), at which time dosing will be decreased to one sachet (500 kcal) daily until discharge as fully recovered. A second trial will enroll 2400 children with MAM and test a standard dose of one daily sachet (540 kcal) of ready-to-use supplemental food against two experimental dosing regimes: one sachet (500 kcal) or two sachets (1000 kcal) of RUTF daily until discharge. Children who recover from these two trials will be randomized again into a third trial evaluating post-recovery protocols designed for the early identification of relapse: (1) the control arm involving one scheduled return visit at 24 weeks post-recovery; (2) the first intervention arm involving three scheduled return visits at 4, 12, and 24 weeks post-recovery; and (3) the second intervention arm which involves caregivers receiving Family MUAC training and one scheduled visit at 24 weeks post-recovery. Discussion This study will provide data on the effectiveness of multiple innovations in the management of childhood acute malnutrition. Results will add to the evidence base on the effectiveness and cost-effectiveness of such modifications in the identification and management of acute malnutrition, ideally adding to the global database on this topic and directly contributing to future WHO guidelines. Trial registration Trials were registered on clinicaltrials.gov as NCT06038071 (registered September 8, 2023), NCT06056089 (registered September 20, 2023), and NCT06061484 (registered September 24, 2023).